Information literacy and formative research: experiences from the Technical University of Manabí, Ecuador - Ruiz Cedeño, Erick; Jalil Vélez, Jorge Ramón; Suástegui Solórzano, Silvia Monserrate (Scripta Mundi, 2026)
Information literacy is a fundamental pillar of contemporary higher education, fostering intellectual autonomy, critical evaluation, and the ethical use of information in learning and research processes. At the Technical University of Manabí (UTM), a gap exists between the academic demands of study programs and students' actual skills in managing scientific and technical information. Given this situation, the study aimed to design a pedagogical strategy that integrates the academic and formative dimensions for UTM. Methods and techniques were applied at both theoretical and empirical levels, emphasizing traditional document analysis and the use of questionnaires administered to faculty and students. The results showed that, while most students demonstrate medium to high levels of information literacy, weaknesses persist in the critical evaluation of sources, the ethical use of information, and the integration of these skills with research practice. Furthermore, the formative value of applied research was confirmed as a means of strengthening autonomous and meaningful learning. It is concluded that the proposed strategy constitutes a viable alternative to integrate information literacy skills into the university curriculum, promoting an academic culture based on reflection, autonomy and responsible knowledge production at the Technical University of Manabí.
Keywords: information literacy; formative research; pedagogical strategy; higher education